Multilocus Sequence Typing and Antifungal Susceptibility of Candida albicans Isolates From Milk and Genital Tract of Dromedary Camel - Fayez, Mahmoud M.; Swelum, Ayman A.; Alharbi, Nada K.; AlRokban, Ahlam H.; Almubarak, Abdullah; Almubarak, Ameen H.; Alaql, Fanan; Ahmed, Ahmed E. (Frontiers in Veterinary Science, 2022)
Multilocus sequence typing (MLST) was used to study the genetic diversity and population structure of 48 Candida albicans (C. albicans) isolates from udder or genital tract of apparently healthy or diseased camels. This study aimed also to determine the frequency of C. albicans isolates in genital tract and udder of healthy or diseased female dromedary camels. A total of 240 mature dromedary camels (230 females and 10 males) were categorized based on the clinical examination of gentile tract and udder into five groups (fertile females (n=70), infertile females (n=115), healthy udder (n=15), mastitis (n=30) and fertile males (n=10). Swabs were collected from male and female genital tract and milk samples were collected from healthy and diseased udders. C. albicans was isolated from 20% of samples. The frequency of isolation was significantly higher (p< 0.00001) in disease camel (75%) compared with apparently healthy camel (25%). Most of C. albicans were isolated from infertile female genitalia (62.50%) which significantly higher than that isolated from fertile female genitalia (16.67%). Multilocus sequence (MLS) analysis identified seven different diploid sequence types (DSTs) including DST2, DST50, DST62, DST69, DST124, DST142 and DST144. The most frequently identified DTS was DST69 (13/48) which significantly higher than DST2, DST62 and DST124. The frequently of identification of DST50, DST142 and DST 144 was significantly higher (p≤ 0.05) than DST62. DST62 and DST124 were isolated only from diseased camels. DST62 was isolated only from mastitic milk. DST124 was isolated only from infertile female genitalia. The percentage of DST50 and DST 142 was significantly higher in infertile females than in the fertile females. DST2 and DST50 were isolated only from female genitalia of apparent health and diseased camels. The C. albicans isolated from diseased camel had significantly higher biofilm formation and phospholipase, proteinase, haemolysin activities compared with than the isolates from apparent healthy camels. All isolates were sensitive to amphotericin B, itraconazole, voriconazole. In conclusion, the present study represents the first molecular typing of C. albicans in samples isolated from milk and genital tract of dromedary camel. MLST is a useful tool for studying the epidemiology and evolution of C. albicans.